Optimized Extraction of H– by Three-Electrode Faraday Cup System in Magnetized Sheet Plasma Ion Source - Fernandez, M. S.; Ramos, H. J. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 15 No 1 (2003), 2007)
A locally designed rectangular parallelepiped, three-electrode Faraday cup system has been developed. Its design incorporates the capability of simultaneous extraction and deposition of the H– ions on substrates. The device functions to attain prescribed selectivity conditions of extracted ions, with controlled energies, for deposition or adsorption. It has been proven to detect the ions at filter bias voltage of 13.61 V with a current density of 5.3 A/m2 that is relatively higher than reported (Abate & Ramos, 2000).